EFFECT OF HIGH STOCKING DENSITY OF INDIAN MAJOR CARPS ON GROWTH, SURVIVAL AND PRODUCTION IN POLY CULTURE SYSTEM - NATH, DHIREN CH.; KALITA, KAMALESWAR (Journal of the Inland Fisheries Society of India, 2021)
In fish culture species combinations, carrying capacity and intensity of management operation are important issues and stocking density often influence the growth. This study tried to investigate the effects of various stocking densities of Indian major carp to the growth performances, survival and total production. The stocking densities tested were 10000 to 50000 fingerlings ha-1 along with 5500 fingerlings ha-1 as control, in eighteen cisterns of 0.003 ha each for a period of 90 days under standard conditions of poly culture system with probable impacts of other environmental criteria. It was recorded that growth of all the species decreased with increase in stocking densities, with mean size of harvest recorded the highest in control group (167.77Â±1.50 g) and the lowest in 50000 fingerlings ha-1 group (74.79Â±1.46 g).Key words: IMC, stocking density, poly culture, fingerling, water quality